(untitled) (International Journal on Stereo & Immersive Media, 2021)
The photographic record of the Alps stretches from the 1840s to the present day and therefore provides visual evidence and significant insight into the devastating impact of global warming on alpine glaciers. In this study, we match photographs from around 1860, 1910 and today, from the same viewpoint, to provide a visual narrative of change in the glaciers of Chamonix Mont-Blanc. During a cooler period in the 16th-19th centuries, now known as the “Little Ice Age”, glaciers descended into alpine valleys and destroyed villages. The most recent maximum of alpine glaciers was attained in the 1820s. They remained fairly close to this maximum until the late 1860s, allowing early photographers to capture them in all their glory. Since then, glaciers have been in general retreat, with shrinkage accelerating on the back of global warming caused by human activity. The speed of change is alarming and is a concern not merely for skiers and alpinists.